The Effects of High-Power Laser Therapy on the Treatment of Patients with Myofascial Trigger Points in the Upper Trapezius Muscle: A Randomized Controlled Trial: High-power laser for the trigger points of upper trapezius - Rahbar, Soulmaz; Radinmehr, Hojjat; Talimkhani, Ailin; Owliaee, Parsa; Montazerlotf, Hanieh; Asadi, Mohammad Reza (Journal of Lasers in Medical Sciences, 2025)
Introduction: This study aims to evaluate the effectiveness of high-power laser therapy (HPLT) in treating myofascial trigger points (MTrPs) in the upper trapezius muscle, a key contributor to myofascial pain syndrome. Methods: This randomized controlled trial enrolled 40 participants with clinically confirmed active MTrPs in the upper trapezius muscle. Participants were randomly allocated to either the HPLT group or the control group. Both groups received ten treatment sessions over a twoweek period. The high- ower laser group was treated using a 15-watt laser device (810/980 nm wavelengths), while the control group received routine physiotherapy. Outcomes (Visual Analog Scale, neck disability, cervical range of motion) were assessed before and after the intervention. Results: Significant improvements were observed in both groups, with the HPLT group showing superior outcomes. Pain intensity in the laser group declined by 4.06 points (6.39±1.65 and 2.23±1.24 before and after the intervention, respectively) compared to 2.33 (7.11±1.88 and 4.78±2.18 before and after the intervention, respectively) in the control group (P<0.001). The Neck Disability Index also showed a more pronounced reduction in the laser group (18.35±6.19 and 6.15±3.64 before and after the intervention, respectively) compared to the control group (21.90±7.49 and 15.50±9.09 before and after the intervention, respectively) (P<0.001). Although both groups showed improved cervical side-bending range of motion (ROM), no significant difference was noted (P>0.05). Conclusion: High-power laser therapy provided significant pain relief and functional neck improvement for individuals suffering from upper trapezius MTrPs. These findings contribute to the growing body of evidence supporting the use of HILT as a viable therapeutic modality for musculoskeletal pain, particularly MTrPs.